(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is a science of life as it defines health and factors responsible for its maintenance and promotion. It is one of the oldest traditional systems of medicine which comprises of thousands of concepts and hypothesis. The primary objective of Ayurveda includes maintenance of health and prevention of diseases. At present, dizziness and vertigo are common symptoms in the patients with the rising prevalence of about 20%. Dizziness is correlated with Murcha in Ayurveda, which is a general feeling of being unstable and fainting whereas vertigo is correlated with Bhrama which is illusion of self and environmental motion. Modern medicines nowadays have harmful impact on health due to their side effects that affect the quality of life. So this is the need of the time that a direct, safe and holistic approach should be established to treat the diseases. The fundamental principles hold a strong ground in Ayurveda. Our Ayurveda classics have mentioned a lot about signs and symptoms of various diseases with their specific herbs. Ayurveda drugs popularity and demand are increasing day by day. Ayurveda drugs are helpful in treating the dizziness (Murcha) and vertigo (Bhrama) through the principles of nature to bring back the individual into equilibrium.